2015
DOI: 10.1007/s00330-015-3894-x
|View full text |Cite
|
Sign up to set email alerts
|

What kind of prostate cancers do we miss on multiparametric magnetic resonance imaging?

Abstract: • The majority of missed prostate cancers were low grade and organ-confined. • In patients with a negative mpMRI a biopsy may be postponed. • mpMRI had a negative predictive value of 95.4 % for high-grade prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 38 publications
2
41
1
3
Order By: Relevance
“…Itatani et al [19] reported a NPV of 89.6 % for mpMRI without significant cancer in a 5-year follow-up study. De Visschere et al [20] found a NPV of 68 % for exclusion of any Gleason grade of prostate cancer, but a very high NPV of 95.4 % for high-grade prostate cancer (Gleason score ≥4 + 3 of any size). Arumainayagam et al [21] showed a NPV of up to 95 % for clinically significant cancer, indicating that MRI may be useful at ruling out clinically significant PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Itatani et al [19] reported a NPV of 89.6 % for mpMRI without significant cancer in a 5-year follow-up study. De Visschere et al [20] found a NPV of 68 % for exclusion of any Gleason grade of prostate cancer, but a very high NPV of 95.4 % for high-grade prostate cancer (Gleason score ≥4 + 3 of any size). Arumainayagam et al [21] showed a NPV of up to 95 % for clinically significant cancer, indicating that MRI may be useful at ruling out clinically significant PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Missed high-grade tumors (primary Gleason ≥4) are predominantly small (66.6% of 18 tumors <1 cm). About 96% of all missed tumors and 83.3% of missed Gleason 4 or greater tumors are organ confined (56). …”
Section: Limitations Of Pretreatment Mpmrimentioning
confidence: 99%
“…Another group examined 830 biopsy-naive patients with elevated levels of prostate-specific antigen. 5 Of the 391 individuals with a negative baseline MRI examination, 124 (31.7%) were diagnosed with PCa during a 2-year follow-up period. In 85.5% of these patients, the primary Gleason grade was 3 or less, and 96.0% had organ-confined disease.…”
Section: The Significance Of a ''Negative'' Prostate Mrimentioning
confidence: 99%
“…For the exclusion of high-grade PCa (ie, primary Gleason grade 4 or any grade 5), MRI had a negative predictive value of 95.4%. 5 In a similar study of 800 patients who underwent prostate MRI, 125 patients had only low suspicion lesions, which were defined as a maximum of 2 positive findings on T2-weighted images, DWI, DCE, or MR-spectroscopy. 6 In none of these cases, biopsy or radical prostatectomy revealed high-risk cancer (ie, !…”
Section: The Significance Of a ''Negative'' Prostate Mrimentioning
confidence: 99%
See 1 more Smart Citation